Factors affecting empathy levels of pharmacy students in Metro Manila - Aguirre, Luis Salvador P.; Aquino, Princess Marie Athena H.; Yap, Regina Marie C.
Empathy is a skill exemplified by healthcare professionals, including pharmacists, which has been shown to promote better patient outcomes. In the Philippines, limited information is present about the empathy levels of students, much less for professionals. This study measured empathy of pharmacy students and determined the factors affecting it. A cross-sectional survey of 252 students was conducted in pharmacy schools in Metro Manila. Demographics, academic background, and psychosocial information were collected using a structured questionnaire. The Jefferson Empathy Scale ? Health- profession student version was used to measure students? empathy. Factors associated with empathy were evaluated using nonparametric analysis. Results showed a mean empathy score of 103.35 ± 15.62. A significant difference in empathy was found across year levels (p=00015). Other factors that were found to be significantly associated with empathy were economic status (p=0.0148), involvement in at least one student organization (p=0.0469), and coming from a public university (p=0.0485). Lower empathy scores were observed in students spending more than five hours daily in student organization activities which implicates the importance of properly balancing academic requirements and organizational duties. In general, pharmacy students in Metro Manila have high empathy levels, which may be attributed to Filipinos being hospitable, resilient, and family-oriented.